AUTOMATIC GIT REPOSITORY DEPLOYER IN UBUNTU USING PYTHON, JENKINS AND CLOUD FIRESTORE AT PT XYZ - Dewangga, Felix Vicky Lugas; Nugraha Saian, Pratyaksa Ocsa (Informatika, Universitas Jenderal Soedirman, 2023)
PT XYZ is a retail company using Cloud Computing to support its business operations. The company requires the back-end application deployment process to be done automatically on each server computer. The problem occurs insecure in the process of the back-end application deployed manually causing human error vulnerabilities and inefficient when the version of application change occurs to operate on each server computer takes time as long as the number of server computers that need to be configured. The research aims to design a deployer system that help company to deploy back-end applications on each Ubuntu server computer automatically efficiently and securely. The research method uses Research and Development to create system. The research produces a design and build of an automated deployer system using Jenkins to create data configuration that aim the version of back-end application as target deploy and stored in the Cloud Firestore database. The stored data causing deployer system change version back-end application as stored data using GIT command and provide application to operate as service on each server computer. Operation result of application recorded as data deployment that stored in the Cloud Firestore then Jenkins detect it to store data as deployment log. Based on the results, the deployer system considered is able to operate back-end application automatically according the target version on each server computer as eficient and secure deployment process. This conclusion is supported by the results of the questionnaire, which obtained a 85% percentage and was classified as